2016 10th European Conference on Antennas and Propagation (EuCAP) 2016
DOI: 10.1109/eucap.2016.7481126
|View full text |Cite
|
Sign up to set email alerts
|

Spherical Near Field offset measurements using downsampled acquisition and advanced NF/FF transformation algorithm

Abstract: Spherical Near Field (NF) measurements are widely used in order to accurately characterize the radiating performance of antennas. The main drawback of this type of measurement is the acquisition time that, depending on the electrical size of the Antenna Under Test (AUT), could be very long. This is due to the fact that, in order to correctly evaluate the Far Field (FF) with the NF/FF transformation [1]-[3], the NF has to be sampled over the full sphere with a sampling density that increases with the dimension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…It must be pointed out that the number of the NF samples collected along the spiral is 36,502 (including the 704 extra samples acquired at reduced spacing nearby the poles) and, accordingly, significantly smaller than that (80,400) needed by the CS NTFFT in the considered case of offset mounting. It should be observed that such a number results to be also lower than the one required by the Foged's technique [36], that would employ an amount of NF data a bit greater than that (45,300) needed by the CS NTFFT when mounting the considered AUT in onset configuration.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It must be pointed out that the number of the NF samples collected along the spiral is 36,502 (including the 704 extra samples acquired at reduced spacing nearby the poles) and, accordingly, significantly smaller than that (80,400) needed by the CS NTFFT in the considered case of offset mounting. It should be observed that such a number results to be also lower than the one required by the Foged's technique [36], that would employ an amount of NF data a bit greater than that (45,300) needed by the CS NTFFT when mounting the considered AUT in onset configuration.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…As can be seen, in both the experimental sets, the number of NF samples to be gathered along the spiral results to be remarkably smaller with respect to the amount of NF data required by the CS NTFFT in the offset mounting case and is also lower than that would be needed when these AUTs are mounted in the onset configuration. Moreover, this number compares favourably also with the one needed by the Foged's technique [36], which, as already stressed, would use an NF data number a bit larger than that required by the CS NTFFT in the onset mounting case.…”
Section: Experimental Assessmentmentioning
confidence: 85%
See 1 more Smart Citation
“…The TSWE is an advanced NF/FF transformation technique to be used in case of SNF measurement with offset AUT. As already pointed out and demonstrated in [9], the advantage of using TSWE in case of offset AUT is the reduction of the number of NF samples to be measured w.r.t. the conventional Nyquist criteria.…”
Section: Translated Spherical Wave Expansionmentioning
confidence: 90%
“…An innovative NF/far-field (FF) transformation algorithm for spherical offset measurements named translated spherical wave expansion (TSWE) has been recently proposed [9,10]. The TSWE is based on the modification of the spherical wave functions, which are properly redefined in a new reference system located on the AUT rather than on the centre of the measurement sphere (as typically done) allowing to drastically reduce the number of samples with a consequent reduction of the testing time.…”
Section: Introductionmentioning
confidence: 99%